Inheritance of grain weight, size and shape in rainfed rice (Oryza sativa) - CHAUHAN, J S (The Indian Journal of Agricultural Sciences, 2013)
Gene effects for grain weight, grain length, breadth and shape (L: 8 ratio) were estimated using means of P1’ P2 F1, F2 and F3 generations of a cross, ’Khaolo 33’ X ’Kalinga III’ of rainfed rice (Oryza sativa L.). The estimates’ of scaling tests, C and D along with joint scaling test mdicated the involvement of inter-allelic interactions in the inheritance of these traits. Dominance gene effects (h) and dominance x dominance (I) interaction were important for grain weight and grain shape. However, grain length and breadth were governed predominantly by additive gene effects (d) and their interaction (I). The number of effective factor pairs controlling these traits varied from 0.13 (grain shape) to 3.86 (grain weight). The estimates of,heritability and genetic advance were fairly consistent for grain length and breadth in ,F2 and F3 generations, whereas there was appreciable reduction for grain weight. ’These characters showed similar trend of relationship in F2 and F3, generations. Selection for grain length could bring forth the correlated improvement in these characters.